Concurrent chemoradiotherapy versus radiotherapy alone for "biopsy‐only" glioblastoma multiforme. Issue 15 (12th May 2016) - Kole, Adam J.; Park, Henry S.; Yeboa, Debra N.; Rutter, Charles E.; Corso, Christopher D.; Aneja, Sanjay; Lester‐Coll, Nataniel H.; Mancini, Brandon R.; Knisely, Jonathan P.; Yu, James B.
Abstract : BACKGROUND: Combined temozolomide and radiotherapy (RT) is the standard postoperative therapy for glioblastoma multiforme (GBM). However, the clearest benefit of concurrent chemoradiotherapy (CRT) observed in clinical trials has been among patients who undergo surgical resection. Whether the improved survival with CRT extends to patients who undergo "biopsy only" is less certain. The authors compared overall survival (OS) in a national cohort of patients with GBM who underwent biopsy and received either RT alone or CRT during the temozolomide era. METHODS: The US National Cancer Data Base was used to identify patients with histologically confirmed, biopsy‐only GBM who received either RT alone or CRT from 2006 through 2011. Demographic and clinicopathologic predictors of treatment were analyzed using the chi‐square test, the t test, and multivariable logistic regression. OS was evaluated using the log‐rank test, multivariable Cox proportional hazard regression, and propensity score‐matched analysis. RESULTS: In total, 1479 patients with biopsy‐only GBM were included, among whom 154 (10.4%) received RT alone and 1325 (89.6%) received CRT. The median age at diagnosis was 61 years. CRT was associated with a significant OS benefit compared with RT alone (median, 9.2 vs 5.6 months; hazard ratio [HR], 0.64; 95% confidence interval [CI], 0.54‐0.76; P < .001). CRT was independently associated with improved OS compared with RT alone on multivariable analysis (HR, 0.71; 95% CI, 0.60‐0.85; P < .001). A significant OS benefit for CRT persisted in a propensity score‐matched analysis (HR, 0.72; 95% CI, 0.56‐0.93; P = .009). CONCLUSIONS: The current data suggest that CRT significantly improves OS in patients with GBM who undergo biopsy only compared with RT alone and should remain the standard of care for patients who can tolerate therapy. Cancer 2016;122:2364–2370 . © 2016 American Cancer Society . Abstract : Data are limited regarding optimal treatments for patients who undergo "biopsy‐only" for glioblastoma multiforme. Outcomes after concurrent chemoradiotherapy versus radiotherapy alone are examined for "biopsy‐only" glioblastoma multiforme using a large national database.